The Impacts of Tax Examinations, Tax Sanctions and Tax Hostage (Gijzeling) on Taxpayers’ Formal Compliance - Puspitasari, Dewi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
The purpose of this study is to determine whether there are impacts of tax audits (X1), tax sanctions (X2), and tax holdings (X3), on formal compliance of taxpayers (Y). The population in this study is the taxpayers registered with KPP Cibitung who live in RW 030 Tambun South. The samples consist of 100 taxpayers using an explanatory sampling method. This type of research is quantitative. The data analysis uses multiple linear regression analysis with SPSS version 25.0 program. Based on data analysis, the results of this study indicate that partially tax audits (X1), tax sanctions (X2), and tax hostage (gijzeling) (X3) have a significant positive effect on taxpayers’ formal compliance (Y). Meanwhile simultaneously tax audits (X1), tax sanctions (X2) and tax hostage (gijzeling) (X3) have significant positive effects on taxpayers’ formal compliance of (Y), with an Adjusted R Square value of 0.444 or 44.4%.